Education as personal development. A Proposal of educational innovation - Araya Alemparte, Domingo Antonio (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
This article exposes an educational innovation which aims to an integral development of the person, taking into account activities that favor the different dimensions of the human beings, particularly emotional and spiritual dimensions, from education for love as the axis of the personal growth of learners.